Needle-knife fistulotomy vs. standard biliary sphincterotomy for choledocholithiasis: common bile duct stone recurrence and complication rate - Archibugi, Livia; Mariani, Alberto; Capurso, Gabriele; Traini, Mariaemilia; Petrone, Maria Chiara; Rossi, Gemma; Testoni, Sabrina Gloria Giulia; Testoni, Pier Alberto; Arcidiacono, Paolo Giorgio (Endoscopy International Open, 2019)
Background and study aims With common bile duct (CBD) stones, access to the CBD can be achieved through the papilla orifice followed by standard biliary sphincterotomy (SBS), or through precut fistulotomy (PF) in case of difficult cannulation. The two methods alter papilla anatomy differently, potentially leading to a different rate of stone recurrence. No data have been published on stone recurrence after PF in patients with CBD stones. The aim of this study was to evaluate CBD stone recurrence, reintervention rate after PF versus SBS, and complications.Patients and methods This was a retrospective single-center cohort study including patients undergoing for the first time endoscopic retrograde cholangiopancreatography (ERCP) for CBD stones with PF in case of failed repeated cannulation attempts, matched for sex/age to patients with SBS randomly extracted from our database. T-test and Fisher’s tests were used for continuous and categorical variable comparison. Recurrence probability was calculated with Kaplan–Meier curve. Factors associated with ERCP repetition were evaluated with logistic regression through a Cox’s proportional hazards model.Results Eighty-five patients with PF were included, with 85 matched controls (mean age 68.7 years, 45.9 % males). Overall, patients with PF had the same reintervention rate as those with SBS (14.1 % vs. 12.9 %) with a hazard ratio (HR) of 1.11 (95 % CI 0.49 – 2.50; P = 0.81), but mean time to reintervention was significantly lower (74.9 ± 74.6 vs. 765.6 ± 961.3 days; P < 0.0001), with 100 % of stones recurring within the first year in the PF group vs. 54.5 % in the SBS group (P = 0.01). The only factor associated with ERCP repetition risk was incomplete CBD clearing. Complications, including pancreatitis, did not differ significantly.Conclusions The reintervention rate was significantly higher in the short term after PF. Therefore, closer follow-up in the first 6 to 12 months after ERCP might be appropriate for patients underoing PF.